Using the chick embryo as a model experiments on the pyrogenic activity of an endotoxin (Experimental biology, 2015)
In this paper, in laboratory studies to uncover mechanisms of action of endotoxin on the development of embryos used chicken embryos. The features and the degree of influence of commercial preparations of LPS and LPS (lipopolysaccharide) derived from cell-free suspension of gram-negative bacteria on the survival and pyrogenicity after a single dose of chick embryos vary depending on the period of ontogenesis. Data were obtained on levellers action nanostructured sorbent krs (carbonized rice husk) in respect of LPS (lipopolysaccharide). Results of experiments on the action of pyrogenic LPS (lipopolysaccharide) of different origin for chicken embryos indicate that administration of LPS suspension leads to hyperthermia (average 2,7 ° C) and mortality (19% on average) compared to control and treated KRS groups.
Keywords: endotoxin; pyrogenicity; chicken embryos; sorbent; elimination